Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm hating these variable resistance questions.

A body of mass $m$ falls from rest in a medium that produces a resistance of magnitude $m\cdot k \cdot v$. where $k$ is a constant, where the speed of the particle is $v$. Show that when the body has reached a speed $V$ it will have fallen for a time

$$\frac{1}{k} \ln \left(\frac{g}{g-k\cdot V}\right) \; .$$

Help much appreciated.

share|improve this question
    
What have you done so far? You should at least be able to get the differential equation(s) which need(s) solving. –  Peter Taylor Feb 16 '11 at 9:45
    
The formula for the time should include big V for the "final" speed. Not small v. –  Raskolnikov Feb 16 '11 at 10:36
    
Shouldn't you ask this at physics? –  Graviton Feb 16 '11 at 13:55

2 Answers 2

up vote 3 down vote accepted

Well the force on the particle due to gravity is $mg,$ where $g$ is the acceleration due to gravity, so the net downward force on the particle is $m(g-kv).$ So its acceleration is $g-kv.$ So you need to solve $dv/dt = g-kv$ given the initial conditions. That is

$$\int_0^V \frac{ \text{d}v}{g-kv} = \int_0^T \text{d}t.$$

share|improve this answer

Okay here is my noob way of solving this (I only learned this less than a year ago but I have forgotten everything and semester starts in a few weeks and I'll probably be required to do this stuff EEEEEEEEEEEEEEEEEEEEEEP),

The forces on the "body" are the resistance and its weight (gravity) as far as I can tell from your description

So $$ \vec{F}_{net} = m\mathbf{a} =mg-mk\mathbf{v} $$

which can be simplified to

$$ \mathbf{a} = g-k\mathbf{v} $$

which can be written in a slightly different form as because acceleration is derivative of velocity

$$ v'(t)+k v(t)=g $$

This looks type of equation looks familiar to me and can be solved as it is a "linear first order differential equation"

Now here is where I may start to make errors so please forgive me

First we multiple everything an "integrating factor" equal to $e^{\int f(t)\,dt}$ where $f(t)=k,$ to make it all work so

$$e^{\int f(t)\,dt}=e^{\int k\,dt}=e^{kt}$$

We don't need a "plus C" (I'm not entirely clear on this but I don't think it makes a difference to anything in the long run, SOMEONE PLEASE CONFIRM)

So when we multiply everything by $e^{kt} $

$$ v'(t)e^{kt}+k v(t)e^{kt}=ge^{kt} $$

which is "equivalent" to this (look at the product rule)

$$ (v(t)e^{kt})'=ge^{kt} $$

Now if we integrate both sides

$$ v(t)e^{kt}={\int ge^{kt}\,dt}$$

$$ v(t)e^{kt}=\frac{ge^{kt}}{k}+C$$

$$ v(t)=\frac{C}{e^{kt}}+\frac{g}{k}$$

To get rid of the C, you said it starts from rest so $v(0)=0$

$$ v(0)=0=\frac{C}{e^{k0}}+\frac{g}{k} = \frac{C}{1}+\frac{g}{k}$$ $$ 0= C+\frac{g}{k}$$ $$ C=-\frac{g}{k}$$

So

$$ v(t)=\frac{-\frac{g}{k}}{e^{kt}}+\frac{g}{k}$$

and I would simplify this to

$$ v(t)=g\frac{1-e^{-kt}}{k}$$

Now Wolfram Alpha would have done this for you

Now to the second part of your question when v(t)=V what is t?

$$ v(t)=V=g\frac{1-e^{-kt}}{k}$$

$$ \frac{kV}{g}={1-e^{-kt}}$$

$$ e^{-kt}=1-\frac{kV}{g}$$

$$ e^{-kt}=\frac{g-kV}{g}$$

$$ e^{kt}=\frac{g}{g-kV}$$

$$ kt=\log_e {\frac{g}{g-kV}}$$

$$ t=\frac{1}{k}\log_e ({\frac{g}{g-kV}})$$

Wolfram Alpha would do this too but is down for me now

I hope this is correct

share|improve this answer
    
I feel dumb after seeing this TOTAL BRAIN FADE –  user7152 Feb 16 '11 at 13:16

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.